1996
DOI: 10.1037/0021-843x.105.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Genital and psychoaffective response to erotic stimulation in sexually functional and dysfunctional men.

Abstract: To understand the sexual response patterns of men with premature ejaculation and erectile dysfunction, the authors compared genital and affective responses of sexually functional and dysfunctional men with 3 types of sexual stimulation: an erotic video, penile vibrotactile stimulation, and a combination of both. Genital response differed across both groups and stimulus conditions, with an interactive effect indicating that groups showed different response patterns depending on the stimulation. Affective respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 27 publications
2
44
1
Order By: Relevance
“…Findings showed that anxiety exerts no significant effect (Beck et al, 1987) or even facilitates sexual arousal in sexually healthy men and women (Barlow, Sakheim, & Beck, 1983;Elliot & O'Donohue, 1997;Laan, Everaerd, Van-Aanhold, & Rebel, 1993;Palace & Gorzalka, 1990), whereas it decreases sexual response in men with sexual problems (Beck et al, 1987). Regarding the impact of mood, research consistently suggests that depressive affect is negativelyrelatedtosexualarousal (Beck&Barlow,1986;Heiman, 1980;Heiman & Rowland, 1983;Koukounas & McCabe, 2001;Meisler & Carey, 1991;Mitchell, DiBartolo, Brown, & Barlow, 1998;Nobre et al, 2004;Rowland, Cooper, & Heiman, 1995;Rowland, Cooper, & Slob, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Findings showed that anxiety exerts no significant effect (Beck et al, 1987) or even facilitates sexual arousal in sexually healthy men and women (Barlow, Sakheim, & Beck, 1983;Elliot & O'Donohue, 1997;Laan, Everaerd, Van-Aanhold, & Rebel, 1993;Palace & Gorzalka, 1990), whereas it decreases sexual response in men with sexual problems (Beck et al, 1987). Regarding the impact of mood, research consistently suggests that depressive affect is negativelyrelatedtosexualarousal (Beck&Barlow,1986;Heiman, 1980;Heiman & Rowland, 1983;Koukounas & McCabe, 2001;Meisler & Carey, 1991;Mitchell, DiBartolo, Brown, & Barlow, 1998;Nobre et al, 2004;Rowland, Cooper, & Heiman, 1995;Rowland, Cooper, & Slob, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, compared with functional counterparts, men with PE report higher negative affect, greater difficulty getting an erection, and weaker overall erections-despite greater selfreported proximity to ejaculation-in response to erotic stimuli. 3,10,11 Such affective states and self-perceptions of erectile response in these men suggest potential disruption of the typical autonomic processes involved in erection and ejaculation. Specifically, parasympathetic action early in the sexual response cycle is typically necessary to initiate and sustain erection, with concomitant or subsequent sympathetic activation responsible in part for mediating ejaculation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that men with concurrent ED and PE often respond differently than men with just ED, both physically and subjectively, to sexual problems and to the therapies directed toward them. 16,17 Materials and methods…”
Section: Introductionmentioning
confidence: 99%